Veiled Muslim women's strategies in response to Islamophobia in Paris. (August 2019) - Najib, Kawtar; Hopkins, Peter
Abstract: This paper explores the spatial and embodied effects of Islamophobia in Paris by focusing on victims' use and adoption of specific strategies in order to avert potential situations of discrimination. We draw upon thirty-three qualitative interviews highlighting the main victims of Islamophobia – young women who wear a headscarf – and present an analysis of their spatial strategies. First, experiences of oppression restrict and limit mobility as veiled women avoid spaces in central, privileged and crowded districts especially when they are alone or with their children. Instead, they use familiar places where they feel comfortable and welcome (such as their neighbourhood or community restaurants and cafés). Second, experiences of oppression have also changed the embodied strategies of veiled women who either feel the need to be strong and integrated, or more discreet and less visible, especially through their clothes. Finally, veiled Muslim women reinvent new mobility and embodied practices in response to geopolitical events; these activist strategies highlight the sophisticated responses of Muslim women in the context of feminist geopolitics and politicisation of their religious faith. This paper hereby contributes to the political and feminist geographies of Muslim women and their multiple negotiations of 'Muslimness' in response to anti-Muslim acts.